Teachers' Pedagogical Adaptation in the Use of Artificial Intelligence in Secondary School Learning - Syarifuddin, Syarifuddin; Lopulalan, Pierre Marcello; Harun, Rudi (PT FORMOSA CENDEKIA GLOBAL, 2026)
The integration of artificial intelligence (AI) in secondary education requires teachers to adapt pedagogically to sustain meaningful learning. This mixed-methods study examines teachers’ pedagogical adaptation in using AI, focusing on learning strategies, assessment, classroom management, and professional readiness. The findings show that effective adaptation is shaped by teachers’ digital competence, institutional support, and prior experience. Teachers who successfully integrate AI adopt learner-centered approaches, use AI for personalized learning and formative assessment, and act as learning facilitators. However, limited training, ethical concerns, and unequal access remain challenges. The study highlights the need for continuous professional development, supportive policies, and clear pedagogical frameworks to ensure AI enhances learning quality.